Methodology of biomechanical monitoring of spatial organization of the human body: justification and testing - Vypasniak, Ihor; Fedyniak, Nazarii (Journal of Education, Health and Sport, 2018)
Relevance. Modern scientific methodology considers monitoring as a multifunctional tool that synthesizes observation, assessment and forecasting. The etymology of the word, which comes from the Latin monitor, indicates its main purpose – the implementation of supervision and control. Unlike general research, monitoring is characterized by focus, allowing to obtain objective empirical data for tracking the dynamics and evolution of the phenomenon under study. Research tasks. To theoretically substantiate the system of biomechanical monitoring of the state of spatial organization of the body of students in the process of physical exercise. Research results. The introduction of the author's correctional and preventive technologies was accompanied by a consistent control system. It included: preliminary control to assess the initial level; operational control to monitor the effectiveness of current actions; current control to assess the results after the completion of individual blocks and semesters; final control of the final assessment of effectiveness for the entire academic year; and self-control to constantly track the dynamics. When organizing the monitoring of the spatial organization of the students' body in the process of physical education, we took into account the fact that it is necessary to have a set of information and methodological tools. Conclusions. Monitoring as a scientific methodology is a comprehensive approach to collecting, analyzing and interpreting data reflecting the state and dynamics of the object of study. In scientific literature, the spatial organization of the human body is understood as a synergetic interaction of morphological and functional aspects, which is reflected in the external form. Thus, the creation of a methodology for biomechanical monitoring of this organization is an urgent scientific task, interdisciplinary in nature. The key feature of biomechanical monitoring of the spatial organization of the human body is its selectivity and target orientation, which allows for effective analysis aimed at specific tasks, as well as tracking the stages of development of the phenomenon under study.